Upaya Meningkatkan Hasil Belajar Siswa Pada Materi Tumbuhan Sumber Kehidupan Melalui Media Konkret Di Kelas IV SDN 55 Palembang - Apriliana, Nuraini; Kalimah, Nur; Aripin, Pipit; Somakim, Somakim; Mindarti, Putri (SJEE (Scientific Journals of Economic Education), 2025)
This research aims to determine the improvement in science learning outcomes regarding Plants as the Source of Life on Earth in class IV students through using concrete objects as media. The aim of this research is to improve the learning outcomes of class IV students in the science subject about Plants, the Source of Life on Earth. The data source for this research is Class IV students at SDN 55 Palembang with a total of 32 students. The research was conducted in semester 1 of the 2024/2025 academic year. The research was carried out for 2 cycles. The data collected is quantitative and qualitative data. Quantitative data is data obtained from the results of formative tests in each cycle. Meanwhile, qualitative data is in the form of observations in each learning cycle. The data obtained is then consulted with the success criteria to determine student learning outcomes. The learning outcomes of students in the first cycle were only 15 students who got a score above the learning objective achievement score. In cycle II it increased to 28 students and the average class score in cycle II was 84.06. Conclusions from research on improving learning using concrete object media can improve the learning outcomes of class IV students in science subjects.